April teachers and teaching professionalism: : building futures (Revista Lusófona de Educação, 2026)
Portuguese teachers who are retiring, or who retired in the last decade, began their professional careers shortly before or shortly after April 25, 1974. How did April 25 and the years that followed shape the careers of these teachers? What aspects of their professional backgrounds and profiles can inform the future of the profession? To answer these questions, biographical-narrative research was conducted, collecting the life stories of 102 teachers who began their professional careers between 1973 and 1983 and who, as ordinary teachers, are recognised by their colleagues as committed. The theory links the concepts of professionalism, socioecologies of teaching identity, and professional life cycles. Inductive thematic analysis resulted in the identification of six themes: pathways; architectures of practice, periods of practice, perceptions, feelings, and factors of change. Two career phases were identified, corresponding to different types of professionalism. Conclusions are drawn about the conditions that favour transformative professionalism.